سمات معلم العلوم المتميز في المرحلة الثانوية من وجهة نظر طلبة السنة التحضيرية في جامعة الملك سعود في ضوء بعض المتغيرات - المومني، جهاد علي توفيق (جامعة الأزهر - كلية التربية, 2015)
هدفت الدراسة التعرف على سمات معلم العلوم المتميز في المرحلة الثانوية من وجهة نظر طلبة السنة التحضيرية في جامعة الملك سعود، وتكونت عينة الدراسة من (335) طالب وطالبة تم اختيارهم بشكل عشوائي من شعب المسار العلمي. ولتحقيق هدف الدراسة قام الباحث بإعداد مقياس مكون من (30) عبارة تمثل أبرز سمات معلم العلوم في المرحلة الثانوية، تم تطبيقه على العينة بعد التأكد من صدقه وثباته. وبعد جمع وتحليل البيانات المتعلقة باستجابات الطلبة على المقياس، أظهرت النتائج: مجيء مجال السمات الشخصية في المرتبة الأولى بالنسبة للذكور يليه مجال السمات العلمية والمهنية ثم مجال السمات الاجتماعية، في حين جاء مجال السمات العلمية والمهنية بالمرتبة الأولى بالنسبة للإناث يليه مجال السمات الشخصية، ثم مجال السمات الاجتماعية. \\ كما أظهرت النتائج وجود فرق ذي دلالة إحصائية بين متوسطي استجابات الطلبة على مقياس السمات في مجالات السمات الشخصية والسمات الاجتماعية لمعلم العلوم تعزى لمتغير النوع، ولصالح الذكور، وعدم وجود فرق ذي دلالة إحصائية بين متوسطي استجابات الطلبة على مقياس السمات تعزي لمتغير نوع التعليم. وبناء على هذه النتائج، فقد خلصت الدراسة إلى مجموعة من التوصيات الهادفة إلى تحقيق التميز في الأداء المهني لدى معلمي العلوم.
This study aimed to investigate the traits of the distinguished secondary stage science teacher from the perspectives of King saud University, preparatory year students. The sample of the Study consisted 335 Participants randomly chosen from King the saud university preparatory year science track students. to achieve the objectives of the study, a 30 item attitude questionnaire representing the major traits of the distinguished secondary stage science teacher was developed by the researcher. The validity and reliability of the questionnaire was assured before distributing it to the sample of the study. The statistical analysis of the participants' responses revealed findings showed that the personal traits domain came first for the male, the scientific and professional domain came second, and the social traits domain came third. Moreover, with regard to the female science teachers, the findings showed that the scientific and professional domain came first, followed by the personal traits domain, and the social traits domain came last. the results also showed there were statistically significant differences between the means of the students' responses on both the personal traits and social traits domains due to the type variable in favor of male science teachers, and There were no statistically significant differences between the means of the students' responses on the traits tool due to the type of education variable. Based on this result, the study concluded that a set of recommendations aimed at achieving excellence in professional performance with the science teacher.
Keywords: طلبة السنة التحضيرية -- جامعة الملك سعود -- التعليم الثانوي -- معلمي العلوم